Zadovoljstvo bolnikov kot element menedžmenta v zdravstveni negi - Bohinc, Marija (Obzornik zdravstvene nege, 1999)
The article present an integrated model comprehensive quality assurance, the important part of which is the quality of health care which is also mentioned in terms of patient satisfaction. Reasons of measuring, its goals and some impediments are being described. Instruments of researching of patient satisfaction in the frames of practice of nursing care are described. The author presents a theoretical model of quality measurement of nursing care from patient's point of view and suggests some direction for new development strategies in nursing care.
Keywords: bolniki; zdravstvena nega; zdravstvene službe